Oposisi dan Koalisi - Munadi Munadi (Resolusi: Jurnal Sosial Politik, 2019)
Democracy allows the people to have equal rights in decision-making that can change their lives. Consequently, opposition and coalition exist in this political system. While the opposition aims to correct and evaluate various government decisions, the coalition is the power holder or supporter of the government. Because Indonesia is a country that uphold legal formal consisting of many political parties, a coalition government party must be formed. This is done by gathering other parties until the government can run effectively so that it has the basis of a combination and effective legitimacy. In the second period of President Susilo Bambang Yudhoyono's cabinet, the emergence of political parties that were powerless and did not dare to become the government's opposition became evidence of the need for democratization. The emergence of elitism, centralization, and anti-public, as well as the freezing of political structures and the backwardness of the cultural attitudes of the Indonesian people caused the opposition to stand on the word of democratization. Therefore coalitions and opposition are two important parts in building a democratic governance system in Indonesia. This article underlines that democracy in the political elite tends to produce a pseudo and half-hearted democracy. Therefor, the portrait of democratization is needed as a reinforcement of all elements of civil society and thus is not seen as a "devout movement of the state", but an urgent movement to change the attitude of the state through changes in the political composition within it.